Triterpenoid saponins from Dianthus chinensis - Hong-Yu, Li; Koike, Kazou; Ohmoto, Taichi (Phytochemistry (Oxford), 1994)
Two novel triterpenoid saponins, dianchinenoside C [23- O-β- d-glucopyranosyl 3β,16α-dihydroxyolean-12-ene 23α, 28β-dioic acid 28- O-β- d-glucopyranoside] and dianchinenoside D [3β,16α-dihydroxyolean-12-ene 23α,28β-dioic acid 28- O-β- d-glucopyranosyl (1 → 6)-β- d-glucopyranoside] were isolated from the aerial parts of Dianthus chinensis. Their structures were determined by spectroscopic methods and chemical evidence. We also report the revision of a previous misassignment of hainanenside, isolated from Ilex hainanensis Merr. In addition, known compounds, 3- O-α- l-arabinopyranosyl hederagenin 28- O-β- d-glucopyranosyl (1 → 6)-β- d-glucopyranoside, sitosterol 3β- O-β- d-glucopyranoside, isoorientin-2″- O-glucoside, isovitexin-2″- O-glucoside, and chrysoeriol-7- O-glucoside, were also identified.